Chronic obstructive pulmonary disease and rheumatic diseases: A systematic review on a neglected comorbidity. (3rd January 2019) - Gergianaki, Irini; Tsiligianni, Ioanna
Background: Although, both chronic obstructive pulmonary disease (COPD) and rheumatic diseases (RDs) are common, and each has significant impact on patients' overall health/quality of life, their co-occurrence has received little attention, while 15% of COPD remains undiagnosed in RDs. Objective: To update the information regarding the comorbid state of RD/COPD (prevalence, incidence), to examine whether patients with RD have increased risk of developing COPD and vice versa, and what implications this comorbidity has on patients' outcomes (mortality, hospitalizations, exacerbations). Methods: We performed a systematic literature review regarding the comorbidity of an RD (rheumatoid arthritis (RA), ankylosing spondylitis (AS), psoriatic arthritis (PsA), systemic lupus erythematosus (SLE), primary Sjogren syndrome disease (pSS), and systemic sclerosis (SSc)) with COPD. From 2803 reports retrieved, 33 articles were further screened. Finally, 27 articles were included. Results: Robust evidence supports that COPD develops up to 68% more frequently in patients with RA, as compared to the general population. Similarly, COPD is increased in every other RD that was studied. Further, self-referred arthritis is more common in COPD patients versus non-COPD controls and a predictor of worst self-rated health status. Patients with inflammatory arthritis/COPD have increased mortality (threefold in RA-COPD, irrespectively of which is first diagnosed), hospitalizations, and emergency visits. Conclusion: COPD is more common in patients with RA, AS, PsA, SLE, pSS, and SSc; yet, the association, vice versa, warrants further investigation. Nevertheless, COPD/RDs coexistence has significant prognostic value for worst outcomes; therefore, awareness is required to track early identification, especially in primary care.